1997
DOI: 10.1055/s-2007-979514
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressant Drug Use: Differences between Psychiatrists and General Practitioners

Abstract: Between 1990 and 1993, a series of drug utilization observation studies with fluoxetine (Flx) were conducted in Germany in several waves. 3,158 patients treated by psychiatrists/neurologists (PN) and 15,601 patients treated by general practitioners/internists (GPI) were included; data collection at start and end of treatment focussed on diagnoses, symptoms, prescription, comedication, efficacy (CGI, Zung scale), and adverse events. Differences between PN and GPI patients were of major interest. For more than 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…All French study which used structured clinical interviews (the MINI) reported that fluoxetine was the most frequently prescribed antidepressant (31.9%) and that the prescriptions were consistent with the guidelines in 76% (major depression 70%, dysthymia 5% and OCD 1%) of the cases (18). A German study found that 90% of the fluoxetine users in psychiatric and general practice had a diagnosis of depression (19).…”
Section: Discussionmentioning
confidence: 99%
“…All French study which used structured clinical interviews (the MINI) reported that fluoxetine was the most frequently prescribed antidepressant (31.9%) and that the prescriptions were consistent with the guidelines in 76% (major depression 70%, dysthymia 5% and OCD 1%) of the cases (18). A German study found that 90% of the fluoxetine users in psychiatric and general practice had a diagnosis of depression (19).…”
Section: Discussionmentioning
confidence: 99%
“…Several phase IV observational studies were conducted with fluoxetine in Germany between 1990 and 1993 (11). These included 3158 patients treated by specialists (psychiatrists/neurologists) and 15 601 treated by generalists (general practitioners or internists).…”
Section: Resultsmentioning
confidence: 99%
“…The majority of patients with mental disorders is seen by general practitioners [1][2][3][4][5][6][7][8]. According to epidemiological surveys, depressed patients were in contact with primary care physicians 14.5 times during the last year but only 1.4 times with psychiatrists [6,8].…”
Section: Introductionmentioning
confidence: 99%